A NEW SPECIES OF APPENDICULA SECTION PODODESME (ORCHIDACEAE) FROM INDONESIA - Aninda Retno Utami Wibowo; Lina Susanti Juswara (Research Center for Biology, 2017)
WIBOWO, A.R.U. & JUSWARA, L.S. 2017. A new species of Appendicula section Pododesme (Orchidaceae) from Indonesia. Reinwardtia 16 (2): 65–71. - A new species, Appendicula cordata (sect. Pododesme) from eastern Indonesia, is described and illustrated. Its habit is similar to that of Appendicula infundibuliformis J. J. Sm., but it differs in having flowers with a cordate appendage and a lip reflexed to the right. An identification key to the species of Appendicula sect. Pododesme, a distribution map, photos and line drawing are also provided.